Durian waste husks as an adsorbent in improving soaking water during the retting process of Piper nigrum l. (pepper berries) - Hamzah, Muhammad Hazwan; Amran, Ainaa Syaheera; Aili Hamzah, Adila Fazliyana; Mohd Nor, Mohd Zuhair; Shamsudin, Rosnah; Che Man, Hasfalina; Wan Razali, Wan Aizuddin (Multidisciplinary Digital Publishing Institute, 2023)
The potential of raw durian husk and NaOH-modified durian husk as an adsorbent, using different doses, 0.5 g, 1.0 g, 1.5 g, and 2.0 g, is investigated to improve soaking water of pepper berries during the retting process. The surface area and the pore size of the durian husk were examined using Brunner Emmett and Teller analysis. The surface area of NaOH-modified durian husk is higher (2.33 m2/g) compared to the raw durian husk (1.51 m2/g). NaOH-modified durian husk has a higher porous structure than the raw durian husk, but both pore diameters are more than 50 nm, which is considered micropore raw material. The effect of the raw durian husk on pH, chemical oxygen demand (COD), dissolved oxygen (DO), and turbidity were compared to the NaOH-modified durian husk with different doses. The 2.0 g of NaOH-modified durian husk enhanced changes in the four parameters. The highest pH value using NaOH-modified durian husk was 6.10 ± 0.02, while turbidity and COD increased to 971.33 ± 1.15 NTU and 1984.67 ± 3.21 mg/L, respectively. The DO of NaOH-modified durian husk shows the lowest reduction to 1.49 mg/L with 2.0 g of NaOH-modified durian husk. The experimental data was best fitted with a first-order kinetic model. Durian husk treated with NaOH could be used as a potential adsorbent to enhance the soaking water for pepper berries.